Question
upstudy study bank question image url

Sirnultaneous Equations Evercise 7: 1) Solve for \( x \) and \( y \) in each of the following equations: a) \( y+6 x=4 \) and f) \( y-x=-6 \) and \[ 2 y=5 x^{2}-22 x+8 \] (b) \( 2 x-y=8 \) and \[ y=x^{2}+4 x-23 \] g. \( y-x=5 \) and \[ 2 x^{2}+5 x y=-2 y^{2} \] \( x y-3 y=8 x-20 \) c) \( y+x=6 \) and h) \[ \begin{array}{l} 2^{x+y}=256 \text { and } \\ x y+3 x+2 y=36 \end{array} \] d) \( 2 x-3 y=2 \) and i) \( 5^{x-2 y-1}=1 \) and \( x^{2}-2 y^{2}=8 \) \[ x^{2}+2 x y-2 x-4 y=0 \] e) \( y-2=2(x-1)^{2} \) and j) \( \cdot(x+5)^{2}+(y-3)^{2}=49 \) and \( y-x=2 \) \( y+x=-9 \)

Ask by Harmon Morrison. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the solutions for each set of simultaneous equations: a) \( y + 6x = 4 \) and \( y - x = -6 \): \[ (x, y) = \left(\frac{10}{7}, -\frac{32}{7}\right) \] b) \( 2x - y = 8 \) and \( y = x^2 + 4x - 23 \): \[ (x, y) = (-5, -18) \text{ and } (3, -2) \] c) \( y - x = 5 \) and \( 2x^2 + 5xy = -2y^2 \): \[ (x, y) = \left(-\frac{10}{3}, \frac{5}{3}\right) \text{ and } \left(-\frac{5}{3}, \frac{10}{3}\right) \] d) \( y + x = 6 \) and \( 2^{x+y} = 256 \): \[ \text{No solution} \] e) \( 2x - 3y = 2 \) and \( x^2 + 2xy - 2x - 4y = 0 \): \[ (x, y) = \left(2, \frac{2}{3}\right) \text{ and } \left(\frac{4}{7}, -\frac{2}{7}\right) \] f) \( y - 2 = 2(x - 1)^2 \) and \( (x + 5)^2 + (y - 3)^2 = 49 \): \[ (x, y) \approx (-0.818, 8.614) \text{ and } (1.952, 3.814) \] g) \( y - x = 2 \) and \( y + x = -9 \): \[ (x, y) = \left(-\frac{11}{2}, -\frac{7}{2}\right) \] h) \( 5^{x - 2y - 1} = 1 \) and \( x^2 - 2y^2 = 8 \): \[ (x, y) = \left(-1 + 3\sqrt{2}, \frac{-2 + 3\sqrt{2}}{2}\right) \text{ and } \left(-1 - 3\sqrt{2}, -\frac{2 + 3\sqrt{2}}{2}\right) \] These solutions provide the values of \( x \) and \( y \) for each pair of equations.

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y+x=6\\2^{x+y}=256\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=6-y\\2^{x+y}=256\end{array}\right.\) - step2: Substitute the value of \(x:\) \(2^{6-y+y}=256\) - step3: Simplify: \(64=256\) - step4: Calculate: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step5: Rewrite: \((x, y) \in \varnothing\) Solve the system of equations \( y-x=2; y+x=-9 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y-x=2\\y+x=-9\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-2+y\\y+x=-9\end{array}\right.\) - step2: Substitute the value of \(x:\) \(y-2+y=-9\) - step3: Add the terms: \(2y-2=-9\) - step4: Move the constant to the right side: \(2y=-9+2\) - step5: Add the numbers: \(2y=-7\) - step6: Divide both sides: \(\frac{2y}{2}=\frac{-7}{2}\) - step7: Divide the numbers: \(y=-\frac{7}{2}\) - step8: Substitute the value of \(y:\) \(x=-2-\frac{7}{2}\) - step9: Calculate: \(x=-\frac{11}{2}\) - step10: Calculate: \(\left\{ \begin{array}{l}x=-\frac{11}{2}\\y=-\frac{7}{2}\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{11}{2}\\y=-\frac{7}{2}\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(-\frac{11}{2},-\frac{7}{2}\right)\) Solve the system of equations \( 5^{x-2 y-1}=1; x^{2}-2 y^{2}=8 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}5^{x-2y-1}=1\\x^{2}-2y^{2}=8\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=2y+1\\x^{2}-2y^{2}=8\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(2y+1\right)^{2}-2y^{2}=8\) - step3: Simplify: \(2y^{2}+4y+1=8\) - step4: Move the expression to the left side: \(2y^{2}+4y+1-8=0\) - step5: Subtract the numbers: \(2y^{2}+4y-7=0\) - step6: Solve using the quadratic formula: \(y=\frac{-4\pm \sqrt{4^{2}-4\times 2\left(-7\right)}}{2\times 2}\) - step7: Simplify the expression: \(y=\frac{-4\pm \sqrt{4^{2}-4\times 2\left(-7\right)}}{4}\) - step8: Simplify the expression: \(y=\frac{-4\pm \sqrt{72}}{4}\) - step9: Simplify the expression: \(y=\frac{-4\pm 6\sqrt{2}}{4}\) - step10: Separate into possible cases: \(\begin{align}&y=\frac{-4+6\sqrt{2}}{4}\\&y=\frac{-4-6\sqrt{2}}{4}\end{align}\) - step11: Simplify the expression: \(\begin{align}&y=\frac{-2+3\sqrt{2}}{2}\\&y=\frac{-4-6\sqrt{2}}{4}\end{align}\) - step12: Simplify the expression: \(\begin{align}&y=\frac{-2+3\sqrt{2}}{2}\\&y=-\frac{2+3\sqrt{2}}{2}\end{align}\) - step13: Evaluate the logic: \(y=\frac{-2+3\sqrt{2}}{2}\cup y=-\frac{2+3\sqrt{2}}{2}\) - step14: Rearrange the terms: \(\left\{ \begin{array}{l}x=2y+1\\y=\frac{-2+3\sqrt{2}}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=2y+1\\y=-\frac{2+3\sqrt{2}}{2}\end{array}\right.\) - step15: Calculate: \(\left\{ \begin{array}{l}x=-1+3\sqrt{2}\\y=\frac{-2+3\sqrt{2}}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=-1-3\sqrt{2}\\y=-\frac{2+3\sqrt{2}}{2}\end{array}\right.\) - step16: Check the solution: \(\left\{ \begin{array}{l}x=-1+3\sqrt{2}\\y=\frac{-2+3\sqrt{2}}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=-1-3\sqrt{2}\\y=-\frac{2+3\sqrt{2}}{2}\end{array}\right.\) - step17: Rewrite: \(\left(x,y\right) = \left(-1+3\sqrt{2},\frac{-2+3\sqrt{2}}{2}\right)\cup \left(x,y\right) = \left(-1-3\sqrt{2},-\frac{2+3\sqrt{2}}{2}\right)\) Solve the system of equations \( y+6 x=4; y-x=-6 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y+6x=4\\y-x=-6\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=4-6x\\y-x=-6\end{array}\right.\) - step2: Substitute the value of \(y:\) \(4-6x-x=-6\) - step3: Subtract the terms: \(4-7x=-6\) - step4: Move the constant to the right side: \(-7x=-6-4\) - step5: Subtract the numbers: \(-7x=-10\) - step6: Change the signs: \(7x=10\) - step7: Divide both sides: \(\frac{7x}{7}=\frac{10}{7}\) - step8: Divide the numbers: \(x=\frac{10}{7}\) - step9: Substitute the value of \(x:\) \(y=4-6\times \frac{10}{7}\) - step10: Calculate: \(y=-\frac{32}{7}\) - step11: Calculate: \(\left\{ \begin{array}{l}x=\frac{10}{7}\\y=-\frac{32}{7}\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=\frac{10}{7}\\y=-\frac{32}{7}\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(\frac{10}{7},-\frac{32}{7}\right)\) Solve the system of equations \( 2 x-y=8; y=x^{2}+4 x-23 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x-y=8\\y=x^{2}+4x-23\end{array}\right.\) - step1: Substitute the value of \(y:\) \(2x-\left(x^{2}+4x-23\right)=8\) - step2: Simplify: \(-2x-x^{2}+23=8\) - step3: Move the expression to the left side: \(-2x-x^{2}+23-8=0\) - step4: Subtract the numbers: \(-2x-x^{2}+15=0\) - step5: Factor the expression: \(\left(-x+3\right)\left(x+5\right)=0\) - step6: Separate into possible cases: \(\begin{align}&-x+3=0\\&x+5=0\end{align}\) - step7: Solve the equation: \(\begin{align}&x=3\\&x=-5\end{align}\) - step8: Calculate: \(x=3\cup x=-5\) - step9: Rearrange the terms: \(\left\{ \begin{array}{l}x=3\\y=x^{2}+4x-23\end{array}\right.\cup \left\{ \begin{array}{l}x=-5\\y=x^{2}+4x-23\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=-5\\y=-18\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=-5\\y=-18\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=-5\\y=-18\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(-5,-18\right)\cup \left(x,y\right) = \left(3,-2\right)\) Solve the system of equations \( y-2=2(x-1)^{2}; (x+5)^{2}+(y-3)^{2}=49 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y-2=2\left(x-1\right)^{2}\\\left(x+5\right)^{2}+\left(y-3\right)^{2}=49\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=2x^{2}-4x+4\\\left(x+5\right)^{2}+\left(y-3\right)^{2}=49\end{array}\right.\) - step2: Substitute the value of \(y:\) \(\left(x+5\right)^{2}+\left(2x^{2}-4x+4-3\right)^{2}=49\) - step3: Simplify: \(21x^{2}+2x+26+4x^{4}-16x^{3}=49\) - step4: Move the expression to the left side: \(21x^{2}+2x+26+4x^{4}-16x^{3}-49=0\) - step5: Subtract the numbers: \(21x^{2}+2x-23+4x^{4}-16x^{3}=0\) - step6: Calculate: \(x\approx 1.952466\cup x\approx -0.818491\) - step7: Rearrange the terms: \(\left\{ \begin{array}{l}x\approx 1.952466\\y=2x^{2}-4x+4\end{array}\right.\cup \left\{ \begin{array}{l}x\approx -0.818491\\y=2x^{2}-4x+4\end{array}\right.\) - step8: Calculate: \(\left\{ \begin{array}{l}x\approx 1.952466\\y\approx 3.814382\end{array}\right.\cup \left\{ \begin{array}{l}x\approx -0.818491\\y\approx 8.613821\end{array}\right.\) - step9: Calculate: \(\left\{ \begin{array}{l}x\approx -0.818491\\y\approx 8.613821\end{array}\right.\cup \left\{ \begin{array}{l}x\approx 1.952466\\y\approx 3.814382\end{array}\right.\) - step10: Check the solution: \(\left\{ \begin{array}{l}x\approx -0.818491\\y\approx 8.613821\end{array}\right.\cup \left\{ \begin{array}{l}x\approx 1.952466\\y\approx 3.814382\end{array}\right.\) - step11: Rewrite: \(\left(x,y\right)\approx \left(-0.818491,8.613821\right)\cup \left(x,y\right)\approx \left(1.952466,3.814382\right)\) Solve the system of equations \( 2 x-3 y=2; x^{2}+2 x y-2 x-4 y=0 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x-3y=2\\x^{2}+2xy-2x-4y=0\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{2+3y}{2}\\x^{2}+2xy-2x-4y=0\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(\frac{2+3y}{2}\right)^{2}+2\times \frac{2+3y}{2}\times y-2\times \frac{2+3y}{2}-4y=0\) - step3: Simplify: \(-1-2y+\frac{21}{4}y^{2}=0\) - step4: Factor the expression: \(\frac{1}{4}\left(-2+3y\right)\left(2+7y\right)=0\) - step5: Divide the terms: \(\left(-2+3y\right)\left(2+7y\right)=0\) - step6: Separate into possible cases: \(\begin{align}&-2+3y=0\\&2+7y=0\end{align}\) - step7: Solve the equation: \(\begin{align}&y=\frac{2}{3}\\&y=-\frac{2}{7}\end{align}\) - step8: Calculate: \(y=\frac{2}{3}\cup y=-\frac{2}{7}\) - step9: Rearrange the terms: \(\left\{ \begin{array}{l}x=\frac{2+3y}{2}\\y=\frac{2}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2+3y}{2}\\y=-\frac{2}{7}\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=2\\y=\frac{2}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{4}{7}\\y=-\frac{2}{7}\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=2\\y=\frac{2}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{4}{7}\\y=-\frac{2}{7}\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(2,\frac{2}{3}\right)\cup \left(x,y\right) = \left(\frac{4}{7},-\frac{2}{7}\right)\) Solve the system of equations \( y-x=5; 2 x^{2}+5 x y=-2 y^{2} \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y-x=5\\2x^{2}+5xy=-2y^{2}\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-5+y\\2x^{2}+5xy=-2y^{2}\end{array}\right.\) - step2: Substitute the value of \(x:\) \(2\left(-5+y\right)^{2}+5\left(-5+y\right)y=-2y^{2}\) - step3: Simplify: \(50-45y+7y^{2}=-2y^{2}\) - step4: Move the expression to the left side: \(50-45y+7y^{2}-\left(-2y^{2}\right)=0\) - step5: Calculate: \(50-45y+9y^{2}=0\) - step6: Factor the expression: \(\left(10-3y\right)\left(5-3y\right)=0\) - step7: Separate into possible cases: \(\begin{align}&10-3y=0\\&5-3y=0\end{align}\) - step8: Solve the equation: \(\begin{align}&y=\frac{10}{3}\\&y=\frac{5}{3}\end{align}\) - step9: Calculate: \(y=\frac{10}{3}\cup y=\frac{5}{3}\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=-5+y\\y=\frac{10}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=-5+y\\y=\frac{5}{3}\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=-\frac{5}{3}\\y=\frac{10}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{10}{3}\\y=\frac{5}{3}\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-\frac{10}{3}\\y=\frac{5}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{5}{3}\\y=\frac{10}{3}\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{10}{3}\\y=\frac{5}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{5}{3}\\y=\frac{10}{3}\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-\frac{10}{3},\frac{5}{3}\right)\cup \left(x,y\right) = \left(-\frac{5}{3},\frac{10}{3}\right)\) Here are the solutions for each of the simultaneous equations provided: ### a) Equations: 1. \( y + 6x = 4 \) 2. \( y - x = -6 \) **Solution:** \[ (x,y) = \left(\frac{10}{7}, -\frac{32}{7}\right) \] ### b) Equations: 1. \( 2x - y = 8 \) 2. \( y = x^2 + 4x - 23 \) **Solution:** \[ (x,y) = (-5,-18) \cup (x,y) = (3,-2) \] ### c) Equations: 1. \( y - x = 5 \) 2. \( 2x^2 + 5xy = -2y^2 \) **Solution:** \[ (x,y) = \left(-\frac{10}{3}, \frac{5}{3}\right) \cup (x,y) = \left(-\frac{5}{3}, \frac{10}{3}\right) \] ### d) Equations: 1. \( y + x = 6 \) 2. \( 2^{x+y} = 256 \) **Solution:** \[ (x, y) \in \varnothing \quad \text{(No solution)} \] ### e) Equations: 1. \( 2x - 3y = 2 \) 2. \( x^2 + 2xy - 2x - 4y = 0 \) **Solution:** \[ (x,y) = (2,\frac{2}{3}) \cup (x,y) = \left(\frac{4}{7}, -\frac{2}{7}\right) \] ### f) Equations: 1. \( y - 2 = 2(x - 1)^2 \) 2. \( (x + 5)^2 + (y - 3)^2 = 49 \) **Solution:** \[ (x,y) \approx (-0.818491, 8.613821) \cup (x,y) \approx (1.952466, 3.814382) \] ### g) Equations: 1. \( y - x = 2 \) 2. \( y + x = -9 \) **Solution:** \[ (x,y) = \left(-\frac{11}{2}, -\frac{7}{2}\right) \] ### h) Equations: 1. \( 5^{x - 2y - 1} = 1 \) 2. \( x^2 - 2y^2 = 8 \) **Solution:** \[ (x,y) = \left(-1 + 3\sqrt{2}, \frac{-2 + 3\sqrt{2}}{2}\right) \cup (x,y) = \left(-1 - 3\sqrt{2}, -\frac{2 + 3\sqrt{2}}{2}\right) \] These solutions provide the values of \( x \) and \( y \) for each pair of equations. If you need further clarification or additional problems solved, feel free to ask!

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

Step back into the world of mathematics, where simultaneous equations have been whispering problems into the ears of curious minds for ages! Did you know that the method of substitution and elimination used to solve these equations has been around since ancient times? Even mathematicians like Isaac Newton and René Descartes dabbled in them! Their tactics have paved the way for modern algebra and have implications in fields from physics to economics. To tackle the exercise at hand, remember that a common pitfall is failing to keep track of signs especially when rearranging equations! It’s helpful to carefully label each step and double-check your arithmetic. Additionally, trying different methods like graphing or using matrices can provide a clearer picture of the solutions you’re nearing—plus, it can turn solving these equations into a bit of an adventure!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy